PENGUJIAN PENTAGON FRAUD TERHADAP KECURANGAN LAPORAN KEUANGAN PADA PERUSAHAAN BADAN USAHA MILIK NEGARA (BUMN) - Kanaya Lapae; Harry Budiantoro; Perdana Wahyu Santosa; Alyta Shabrina Zhusrin (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2022)
This study aims to examine the effect of pentagon fraud on financial reporting in State-Owned Enterprises (BUMN) on the Indonesia Stock Exchange in 2016-2020. In this study, the sample collection used purposive sampling technique by determining certain criteria and obtained as many as 85 samples from 17 state-owned companies. The data used is secondary data in the form of the company's annual report. The data analysis method used is the multiple linear regression method using the SPSS 25.0 application. The results showed that external pressure, financial targets and the nature of the industry had a significant effect on financial statements. As for finance, auditor turnover, board turnover, CEO and CEO image frequency have no effect on financial statements. Keywordsi: pentagon fraud, fraud, fraudulent financial statement